Improving Marketing Performance Through Competitive Advantage in Phase Two Of The Covid-19 Pandemic - Maulana Ichsan; Naili Farida; Sari Listyorini (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
The marketing performance of small and medium businesses in the Ancol tourism area is influenced by an effective market strategy so that they are able to realize a competitive advantage. The purpose of this study is to examine market strategies in competitive advantage, and their implications for marketing performance in small and medium businesses in the Ancol tourism area. The sample research technique uses Probability Sampling. The sample selection technique in this study used Proportional Random Sampling with the sample in this study amounting to 235 small and medium businesses in the Ancol area during the Covid-19 pandemic from 70 small and medium businesses with a scale of 1 to 10 questionnaires to find out the interpretation of market strategies, competitive advantage, and marketing performance. The data technique was analyzed using multiple linear regression with the intervening test. Research statement: "that the problem stems from the marketing performance of small and medium enterprises in the Ancol tourist area as a dependent variable which is influenced by competitive advantage as an intervening variable and market strategy, as well as research that is new in nature which is a research topic that has never been done by previous researchers. Research findings indicate that marketing performance is influenced by market strategy through competitive advantage. Based on the results of the study, it can be concluded that market strategy has an effect on competitive advantage. Alignment of market strategy produces a greater influence on competitive advantage. Market strategy affects marketing performance through ineffective competitive advantage in its role as an intervening variable between market strategy and marketing performance. From this phenomenon, the research looks at the relationship of variables through literature review and the marketing performance literature approach. This paper provides definitions, dimensions, and determinants of market strategies to improve marketing performance through optimizing competitive advantage.